Design, Development, and Antitumor Potential of CD228-Targeted Antibody–Drug Conjugates - Qiu, Haitao; Xie, Liping (Pharmaceutical Fronts, 2025)
Melanotransferrin (CD228) is a membrane glycoprotein involved in tumor growth and metastasis and is highly expressed in various solid tumors. Despite its tumor-specific nature, no antibody drugs targeting CD228 are currently available. This study aimed to develop a humanized CD228 monoclonal antibody and its antibody–drug conjugate (ADC) to evaluate in vitro cytotoxicity and in vivo antitumor efficacy against melanoma. In this work, mice were immunized with the extracellular domain of CD228, and specific antibodies were screened using hybridoma technology, followed by humanization. The humanized antibody was conjugated to monomethyl auristatin E (MMAE) with a citrulline–valine linker and purified by protein A chromatography. The drug–antibody ratio (DAR) and purity were analyzed using hydrophobic interaction chromatography and size-exclusion chromatography. CCK8 assay was performed to assess cytotoxicity against tumor cells, and antibody-dependent cell-mediated cytotoxicity (ADCC) was assessed using Jurkat cells. An A2058 melanoma xenograft model was used to examine in vivo efficacy. This work identified a humanized antibody, Ab-2F6A1, with high CD228 binding affinity, with EC50 values of 1.746 ng/mL (protein binding activity) and 83.8 ng/mL (cell binding activity). The ADC, Ab-2F6A1-VcMMAE, had an average DAR of 4.9026 and a purity of 98.24% and showed significant in vitro cytotoxicity against melanoma, breast, and colon cancer cells. Ab-2F6A1-VcMMAE has a stronger ADCC effect compared with the positive control (Ab-hI49-VcMMAE), and exhibited superior melanoma tumor inhibition in vivo. Given the above, a novel humanized anti-CD228 antibody and its ADC were successfully developed. The ADC demonstrated strong antigen binding, in vitro antitumor activity, ADCC effects, and superior in vivo melanoma inhibition, supporting CD228 as a promising therapeutic target.
Keywords: melanocyte transferrin; hybridoma; antibody humanization; antibody–drug conjugate; antitumor activity